2008
DOI: 10.1002/gps.1973
|View full text |Cite
|
Sign up to set email alerts
|

A 6‐month, open‐label study of memantine in patients with frontotemporal dementia

Abstract: The number of patients was small, so that the evidence given by statistical tests is limited. Thus, the present study can only show trends regarding drug effects. As memantine is well-tolerated, further randomized and controlled studies should be conducted to evaluate drug efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 33 publications
1
47
1
4
Order By: Relevance
“…Memantine is usually prescribed for bvFTD patients by half of the physicians surveyed in this study. Some recent preliminary studies have argued for the benefits of this uncompetitive antagonist of the N-methyl-D-aspartate glutamate receptor on the behavioral disturbances of bvFTD patients (Boxer et al 2009;Diehl-Schmid et al 2008;Kavirajan 2009;Swanberg 2007;Vossel and Miller 2008). Nonpharmacological treatment was usually indicated by almost half of the participants in this study, who also very frequently suggested psychotherapy for relatives of bvFTD patients.…”
Section: Diagnosis and Treatment Of Bvftdmentioning
confidence: 88%
“…Memantine is usually prescribed for bvFTD patients by half of the physicians surveyed in this study. Some recent preliminary studies have argued for the benefits of this uncompetitive antagonist of the N-methyl-D-aspartate glutamate receptor on the behavioral disturbances of bvFTD patients (Boxer et al 2009;Diehl-Schmid et al 2008;Kavirajan 2009;Swanberg 2007;Vossel and Miller 2008). Nonpharmacological treatment was usually indicated by almost half of the participants in this study, who also very frequently suggested psychotherapy for relatives of bvFTD patients.…”
Section: Diagnosis and Treatment Of Bvftdmentioning
confidence: 88%
“…119 For the management of cognitive symptoms related to FTD, several open label studies have demonstrated benefit in patients who were treated with NMDA antagonist (memantine) with doses up to 20mg/day. 120 In an open label study of 16 121 However a recent RCT of 81 patients did not demonstrate a clear benefit with NMDA antagonist (memantine). 122 The choice of acetylcholinesterase inhibitors should be based upon factors such as experience of the clinician, tolerance to side effects, ease of use, and the clinical profile of the individual to be treated.…”
Section: Frontotemporal Dementiamentioning
confidence: 98%
“…[26][27][28]30,32,34 However, the Bromocriptine study showed a significant improvement in the mean time of utterance as compared to the placebo, 31 and one Memantine study found a significant increase in the total score of ADAS-Cog. 35 36 Two B studies did not evaluate cognitive functions. 12,33 The quality C studies showed a significant improvement in behavior with Selegiline.…”
Section: Resultsmentioning
confidence: 99%